BERUGAK SEBAGAI ARUS KOMUNIKASI DAN INFORMASI BAGI MASYARAKAT SASAK LOMBOK - Supriadi (Mudabbir: Jurnal Manajemen Dakwah, 2024)
The Sasak Tribe community on Lombok Island is part of a community that has high social relations, especially in terms of kinship and friendship that is always established in every level of society. One of the favorite zones of the Sasak people to strengthen social relations is to gather in one of the typical buildings that have a fairly high cultural architectural value, namely berugak, either berugak in the form of sekepat or sekenem. This gazebo-shaped building made of wood or bamboo for the Sasak community is not just a seat but a place for communication and information exchange between communities, both planned and unplanned. Departing from this community communication activity is what led the author to study in depth what the flow of communication and information that is built in the midst of a community that communicates through berugak.The method used by the author or researcher in studying berugak as a flow of communication and information for the Sasak community of Lombok is to use exploratory qualitative type research which researchers want to see formulation of communication and information flows used by the Sasak community because broadly speaking researchers do not have a clear picture of the situation and type of communication used by the Sasak Tribe community and what the flow of information circulation is like in the Sasak Tribe community, especially in the use of berugak as a medium for communication.Finally, after conducting an in-depth study of this study, researchers were able to find the results that berugak for the community has a multifunction between, as a family room, study room, discussion room and even a place to live. Then various communication models can be formed through berugak according to the interests and position of the location such as interpersonal communication, group communication, organizational communication, political communication and public communication. The type of information obtained by the Sasak community through berugak is pure information from problems that occur in the midst of the Sasak Tribe community and there is also information that is continued information from news originating from mass media, social media.